Examining the paradox of occupational stressors : building resilience or creating depletion - Perrewé, Pamela L.; Harms, Peter D.; Chang, Chu-Hsiang (Daisy) (Research in occupational stress and well being ;, 2022)
Volume 20 of Research in Occupational Stress and Well Being features contributions that expand the understanding of how occupational stressors can build employee resilience and enhance their well-being while at the same time creating negative employee outcomes such as depletion, exhaustion, and depression. To this end, chapters take a hard look at examining the outcomes of work stressors, the circumstances or conditions that can change or even reverse the relationship between stressors and outcomes, and theoretical accounts for apparent contradictions in this literature. Examining the Paradox of Occupational Stressors: Building Resilience or Creating Depletion represents insightful, intriguing, and timely research into the paradox of experienced stress in the workplace.